Multifunctional and Tunable Radar Absorber Based on Graphene‐Integrated Active Metasurface. Issue 4 (24th February 2021) - Huang, Cheng; Ji, Chen; Zhao, Bo; Peng, Jinqiang; Yuan, Liming; Luo, Xiangang
Abstract: In this article, a multifunctional and tunable radar absorber which can achieve dynamical modulation of absorbing frequency, bandwidth, and amplitude is presented. Such a tunable radar absorber is composed of a graphene capacitor layer and an active metasurface layer. By controlling the impedance characteristic of each layer through the external bias voltages, the absorber not only can achieve the ultrawideband electromagnetic (EM) absorbing performance, but also can be switched to a narrowband absorption mode, and its absorption amplitude can be further adjusted at each of the above operation modes. Both simulated and experimental results have demonstrated that the −10‐dB reflection bandwidth ranging from 3.55 to 19.6 GHz can be realized, and the average reflection amplitude can be dynamically tuned between −3.8 and −11.5 dB. In addition, by changing the bias voltages, the absorber can also, respectively, switch its −10 dB reflection bandwidth to 3.5−11.1 GHz and 10.9−18.9 GHz, where the larger dynamic range of amplitude modulation is obtained. The equivalent circuit model is employed to explain the tunable absorption mechanism by analyzing the impedance matching characteristics. This hybrid design approach can effectively expand the EM reconfigurable functionalities of the current tunable absorber, which may further open a novel way of the graphene application in microwave frequencies. Abstract : A multifunctional and tunable radar absorber is proposed based on a combination of graphene capacitor layer and active metasurface layer. By electronically tuning the impedance characteristic of each layer, such an absorber can dynamically switch its −10 dB absorbing bandwidth bewteen ultra‐wideband and narrowband modes, and its absorption amplitude can be further adjusted at each operation mode.